2017
DOI: 10.1017/s1751731116001324
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of high milking frequency during the first 21 days of lactation on production and reproductive performance in high-lactating cows

Abstract: We examined short-and long-term effects of high milking frequency (HMF) for the first 21 days of lactation. The study included 122 Israeli Holstein cows -32 pregnant heifers, 40 cows in second lactation and 50 cows in >second lactation. Heifers were paired according to predicted transmitting ability and cows according to energy-corrected milk (ECM) production, age, days in milk and expected calving date. Thin cows (body condition score < 2.75) were not included. One cow from each pair was arbitrarily allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Although a flattened lactation curve appeared for half-udders subjected to IM, we did not examine the effects of incomplete milking after we terminated our treatment protocol at 47 DIM. A positive carryover effect of IMF during early lactation on milk production has been observed previously (Bar-Peled et al, 1995;Soberon et al, 2011;Shoshani et al, 2017). Because IMF involves more frequent removal of milk from the mammary gland and incomplete milking involves removing a smaller volume of milk, it can be reasoned that incomplete milking could have a negative carryover effect on milk production.…”
Section: Discussionmentioning
confidence: 72%
“…Although a flattened lactation curve appeared for half-udders subjected to IM, we did not examine the effects of incomplete milking after we terminated our treatment protocol at 47 DIM. A positive carryover effect of IMF during early lactation on milk production has been observed previously (Bar-Peled et al, 1995;Soberon et al, 2011;Shoshani et al, 2017). Because IMF involves more frequent removal of milk from the mammary gland and incomplete milking involves removing a smaller volume of milk, it can be reasoned that incomplete milking could have a negative carryover effect on milk production.…”
Section: Discussionmentioning
confidence: 72%
“…Moallem et al ( 2019) compared 2× with 3× milking in the first 30 DIM and found improvements in energy balance without lasting negative effects on milk production when cows were milked 2×. Increase in milking frequency from 3× to 6× in the first 21 DIM has been investigated by others (Shoshani et al, 2017), with long-lasting increases in milk production in cows milked 6×. Effects on BCS were parity dependent with a lower BCS in the 6× group in second-lactation cows only.…”
Section: Housing and Managementmentioning
confidence: 99%
“…Additional emphasis has been given to milking machine effects and examining the resistance of the teat canal itself to bacterial invasion, considering factors such as overmilking, milk flow, vacuum level, liner slips, and pulsation (Thompson et al, 1978;Natzke et al, 1982;Baxter et al, 1992;Lacy-Hulbert and Hillerton, 1995;Wieland et al, 2018). Research has also focused on the potential dispersal of bacteria in the udder by considering factors such as hand-stripping to remove foremilk and the frequency of udder evacuations (Mein et al, 2004;Shoshani et al, 2017). Other external factors, such as cow age, season, and climate have also been examined for their influence on the occurrence of mastitis (Fox et al, 1995;Bates and Dohoo, 2016;Zhang et al, 2016).…”
Section: A Critical Issue For the Dairy Industrymentioning
confidence: 99%